Synthesis of 5-(Trifluoromethyl)-2,5-dihydro-1,2λ5-oxaphospholes by a One-Pot Three-Component Reaction - Fan, Hua-Fang; Wang, Xiao-Wei; Zhao, Jing-Wei; Li, Xin-Jin; Gao, Jin-Ming; Zhu, Shi-Zheng (Synthesis, 2012)
A series of trifluoromethyl-substituted 1,2λ5-oxaphospholes were prepared in yields of up to 95% by a one-pot three-component reaction under mild conditions. The zwitterionic intermediate generated by attack of triphenylphosphine on an alkyl propiolate reacts with an aryl or styryl trifluoromethyl ketone to form the 1,2λ5-oxaphosphole ring. All the new products were characterized by IR, NMR, and mass spectroscopy and the structure of one of them, ethyl 2,2,2-triphenyl-5-[(E)-2-phenylvinyl]-5-(trifluoromethyl)-2,5-dihydro-1,2λ5-oxaphosphole-4-carboxylate, was confirmed by X-ray single-crystal diffraction analysis.
Keywords: heterocycles; phosphorus; fluorine; oxaphospholes; alkynes; ketones